Strategi Sosialisasi dan Sanksi Perpajakan sebagai Upaya Meningkatkan Kepatuhan Wajib Pajak: Studi Kualitatif Multi-Tahun - Deni Iskandar (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2026)
This study critically examines the role of tax socialization strategies and the enforcement of tax sanctions in enhancing taxpayer compliance in Indonesia. Adopting a qualitative research design, the study employs multi-year secondary data covering the period 2015–2024. Data were derived from official reports of the Directorate General of Taxes (DGT), publications from DDTC News and Kontan, as well as relevant empirical studies. The analysis emphasizes trends in annual tax return (SPT) filing compliance, the configuration and intensity of tax socialization initiatives, the typology of sanctions imposed, and the dynamic interrelationship between socialization efforts, sanction enforcement, and compliance behavior. The findings indicate a generally upward trajectory in taxpayer compliance throughout the observation period, notwithstanding fluctuations influenced by macroeconomic conditions and fiscal policy developments. Tax socialization proves more effective when implemented through an integrated framework that synergizes digital dissemination channels, direct outreach programs, and improvements in administrative service quality. Furthermore, administrative penalties, criminal sanctions, and enforced collection measures serve as deterrent mechanisms that reinforce compliant behavior. The interaction between persuasive instruments (socialization) and coercive mechanisms (sanctions) suggests that a comprehensive and integrated policy approach generates more sustainable compliance outcomes than isolated interventions. These findings offer practical implications for the Directorate General of Taxes in formulating adaptive, technology-driven socialization strategies, ensuring consistent and proportional sanction enforcement, and strengthening service quality to promote sustainable taxpayer compliance.